A Chronic Sialolithiasis of the submandibular gland with a gigantic collection of stones - A Case Report - Khan, Sher Ali; Elkony, Anas Ahmed (Journal of Rawalpindi Medical College, 2025)
Sialolithiasis, characterized by the accumulation of calcium salt deposits known as sialoliths, often affects the submandibular gland nestled within the submandibular triangle. This disorder primarily impacts the submandibular gland due to the lower positioning of Wharton's duct, facilitating retrograde infection by oral flora. The alkaline saliva produced by the gland actively promotes the precipitation of calcium salts, consequently fostering the formation of sialoliths. This case study showcases a 35-year-old male patient who developed a huge sialolith and persistent sialadenitis after recurring submandibular swelling and pain. The patient revealed a ten-year history of recurrent painful, persistent swelling and a gradual increase of dysphagia during his last seven-month illness. Chronic sialolithiasis was diagnosed when imaging revealed a large sialolith collection. A contrast-enhanced neck CT confirmed a massive intra-parenchymal stone aggregate and an enlarged gland. Following submandibular sialoadenectomy, unusually shaped stones weighing 189 grams were discovered. A histopathological study confirmed the presence of squamous and mucinous metaplasia together with persistent sialadenitis, ruling out cancer. At the three-month follow-up, the patient showed favorable healing and improved speech. The objective is to highlight a gigantic collection of stones with unusual presentation in submandibular sialolithiasis, clinical features, diagnostic techniques, and treatment options. Highlighting the complexities of submandibular sialolithiasis, this case report emphasizes the need for early and easy access to timely healthcare provision in getting precise diagnoses and tailored treatment plans and avoiding complications related to delayed and unreachable healthcare. Successfully performing a submandibular sialoadenectomy led to significant relief of symptoms, demonstrating the effectiveness of surgical approaches in managing chronic sialadenitis with large sialoliths.